The dynamics of marital relationship after infidelity: Phenomenological descriptive analysis on Muslim spouses - Muhammad Zulfa Alfaruqy; Endang Sri Indrawati (INSPIRA: Indonesian Journal of Psychological Research, 2023)
An unstable marital relationship, including an Islamic spouse, opens up opportunities for extramarital affairs. This study aimed to understand the dynamics of the relationship between a Muslim husband and wife who face a wife’s infidelity. This research uses qualitative methods with a phenomenological approach. The subject criterion is a Muslim wife who has had an affair and is still married. Three subjects were selected through a purposive sampling technique. Data collection using a semi-structured interview. The results show that the background of the wife’s infidelity is multi-factor. Marital relations reflect the interdependence of husband and wife. This relationship becomes more dynamic and complex because of the presence of a third person. During an affair, the relationship is under an actor’s control. The relationship transforms into a controlling partner after the affair. Wives initiate nonmutual relations manifested in permissive behavior towards husbands as an effort to atone for guilt and maintain a marriage. The research has theoretical implications for religion and supports the effect of social norms in reading the interdependence of marital relations between Islamic husband and wife.